Dampak Penggunaan Aplikasi BRImo Terhadap Prilaku Konsumtif Mahasiswa Institut Agama Islam Edi Haryono Madani Riau (INSTITUT EHMRI) - Reynaldi, Reynaldi; Munthe, Marabona (EL-EMIR Institute, 2024)
This research aims to identify the influence of using the Brimo application on the consumer behavior of students at the EHMRI Islamic Institute (IAI). The Brimo application is a digital banking platform that provides various conveniences in financial transactions, such as fund transfers, payments and checking balances. This research uses quantitative methods with a survey design. The research sample consisted of 100 IAI EHMRI students who used the Brimo application. Data was collected through a questionnaire that measured the level of consumer behavior before and after using Brimo. Based on the output above, the tcount value is 16,060, while the ttable value is 1.668. This explains that tcount (16,060) > ttable (1.668) with sig 0.000 < sig 0.05 so it can be concluded that there is a significant influence of BRIMO on the Effect of using Brimo on the Consumptive Behavior of IAI Students. The results of this study indicate that the use of Brimo can provide maximum benefits if balanced with increased awareness and good financial management by students.